Association of Underweight and Hand Grip Strength with the Risk of All-cause Mortality in Older Adults - Min-jun Kim; Tae-woong Oh (Korea Institute of Sport Science, 2023)
PURPOSE This study investigated the impact of underweight and hand grip strength (HGS) levels on the risk of all-cause mortality in older adults. METHODS Data from the 2006 baseline and 2020 follow-up assessments of the Korean Longitudinal Study of Aging (KLoSA), involving 3,009 older Koreans (≥65 years) were used in the study. Participants were categorized based on body mass index (BMI) as underweight, normal, overweight, or obese and grouped according to the Asian Working Group Sarcopenia criteria into high or low HGS. Cox proportional hazard models were used to estimate the hazard ratio (HR) and 95% confidence interval (CI) of all-cause mortality according to BMI and HGS categories. RESULTS During the 11.3±4.0 years follow-up period, 1,334 deaths from all causes occurred. The risk of death by BMI and HGS level was analyzed. The results showed that the risk of death in the overweight and high HGS group (HR=0.773, p=.016) was significantly lower than that in the normal weight & high HGS group (HR=1). In comparison, the risk of death in the underweight & low HGS group (HR=1.930, p<.001) and the normal weight & high HGS group (HR=1.225, p=.014) were significantly higher than normal weight & high HGS. However, the risk of death in the underweight and high HGS group showed no significant difference compared to the normal weight and high HGS group. CONCLUSIONS The current findings suggest that improving muscle strength through regular exercise may be important in preventing the risk of all-cause mortality due to being underweight.